Tumor resident microbiota and response to therapies: An insight on tissue bacterial microbiota - Pirini, Francesca; Cortesi, Michela; Tumedei, Maria Maddalena; Zanoni, Michele; Ravaioli, Sara; Bravaccini, Sara (Frontiers in Cell and Developmental Biology, 2023)
The role of the intestinal microbiota in the promotion, progression, and response to therapies is gaining importance, but recent studies confirm the presence of microbiota also in the tumor, thus becoming a component of the tumor microenvironment. There is not much knowledge on the characteristics and mechanisms of action of the tumor resident microbiota, but there are already indications of its involvement in conditioning the response to therapies. In this review, we discuss recent publications on the interaction between microbiota and anticancer treatments, mechanisms of resistance and possible strategies for manipulating the microbiota that could improve treatments in a personalized medicine perspective.